Evaluation of Oxidative Stability of Vegetable Oils during Deep Frying - Almrhag, Omar; Abookleesh, Frage (Arab Journal for Sciences and Research Publishing, 2016)
The oxidative degradation of the used oils were evaluated by monitoring total polar compound (TPC), Iodine value (IV), Peroxide value (Pv), specific extinction E1% at 233nm and 269nm, and changes in the fatty acids profile. Three different types of edible oils, namely, corn oil, soybean, and palm olien, were used in deep fat frying at 180 oC ± 5oC for 5 h/d for three consecutive days. The result of this study indicates that palm olein showed significantly (P<0.05) lower in all measured parameters than the other oils used. For PV, the rate of increase was not constant as frying progressed. The extent of oil deterioration was best reflected in the changes in percent TPC, IV, E1%cm at 233nm.